The role of U.S. pharmacists in deprescribing: Recommendations based on a systematic literature review of qualitative studies - Alina Cernasev; Devin Scott; Becka Eckert; Hilary Jasmin; David R. Axon (Exploratory Research in Clinical and Social Pharmacy, 2025)
Purpose: Deprescribing is increasingly investigated through a qualitative lens, yet no evidence synthesis of the extant qualitative deprescribing literature exists. This study aimed to identify and synthesize relevant qualitative data about the role of the pharmacist or pharmacy profession in deprescribing in the United States. Methods: A systematic literature review was conducted in July 2024 in MEDLINE (PubMed), Scopus (Elsevier), and Embase (Elsevier). The primary search concepts included terms around pill burden, cessation and de-prescription, as well as a search string to narrow results to qualitative reports. From 4410 unique records after deduplication, 46 abstracts were included for full text review. Results: After full text review, 11 records were deemed suitable for inclusion in this review. Three used interviews, five used focus groups, and three used both. Three studies used the theory of planned behavior, two studies used the capability, opportunity, and motivation behavior model, one used the chronic care model, one used the interprofessional shared decision-making model, one used grounded theory, and three did not use a framework. Studies were conducted in New York (n = 3), Arizona, Maine, and Tennessee (n = 3), California (n = 1), Iowa (n = 1), Massachusetts (n = 1), North Carolina (n = 1), and Rhode Island (n = 1). Key themes identified across the studies included enablers, obstacles, process of deprescribing, and deprescribing in pharmacy education. Conclusions: Deprescribing is a complex process that involves the entire healthcare team, including pharmacists who have unique expertise to support the team through education and information about medication and disease states.